Mechanical Properties of Polypropylene (PP) – Montmorillonite (MMT) Nanocomposites for Pre-Fabricated Vertical Drain (PVD) Application - Selamat, N.A.; M.Ansari, M.N.; Yahya, Zainudin; E.Naicker, Ragunatha (International Journal of Engineering and Technology, 2018)
Polypropylene (PP) – montmorillonite (MMT) blends were prepared by melt-mixing method followed by injection molding method. The optimum process melt-temperature was set at 1950C, the injection speed of 15cc/s, injection pressure of 30MPa and cooling time of 20 sec. was used for the sample preparation. Investigation shows, addition of MMT nanoparticles have improved the mechanical properties. The tensile test and impact test were conducted at room temperature and atmospheric pressure. The tensile modulus and yield strength improved with increasing MMT content, however, elongation at break was reduced as the MMT content was increased from 2wt% to 8wt%. The Izod impact strength is also affected by the addition of MMT content. Nanocomposites based on PP containing 8wt% of MMT showed higher impact strength than the other compositions and Neat PP (control). The influence of MMT content on impact strength increased with MMT content which is a significant result required for pre-fabricated vertical drain (PVD). Further investigations are required to study the mechanical properties of the PVD using PP – MMT nanocomposites to replace the existing material (PP).